2019
DOI: 10.2147/idr.s189341
|View full text |Cite
|
Sign up to set email alerts
|

<p>Emergence of multidrug resistance and extensive drug resistance among enterococcal clinical isolates in Egypt</p>

Abstract: Introduction Enterococci commonly inhabit the gastrointestinal tract of both human and animals; however, they have emerged as a leading cause of several infections with substantial morbidity and mortality. Their ability to acquire resistance combined with intrinsic resistance to various antimicrobials makes treatment of enterococcal infections challenging. Materials and methods The aim of the study was to evaluate the antimicrobial resistance pattern, and assess the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 66 publications
5
23
2
3
Order By: Relevance
“…As regards Enterococci , the overall resistance pattern was comparable to that reported by Said and Abdelmegeed [ 29 ] with the exception of the higher linezolid resistance reported (9.7%) in their study. Likewise, the resistance pattern of ciprofloxacin, erythromycin, gentamicin, and linezolid agrees with that reported by Zalipour and coworkers [ 30 ].…”
Section: Discussionsupporting
confidence: 87%
“…As regards Enterococci , the overall resistance pattern was comparable to that reported by Said and Abdelmegeed [ 29 ] with the exception of the higher linezolid resistance reported (9.7%) in their study. Likewise, the resistance pattern of ciprofloxacin, erythromycin, gentamicin, and linezolid agrees with that reported by Zalipour and coworkers [ 30 ].…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of VRE isolates in our study was relatively low compared with that found in India (7.0%) ( Bhatt et al., 2015 ) and in Egypt (6.3%) ( Said & Abdelmegeed, 2019 ), indicating that risks of VRE infections may be associated with geographic variability. Blanco et al (2017) reported in 2017 that relative humidity and geographical location were factors affecting VRE colonization rates in adult patients admitted to ICUs in the United States.…”
Section: Discussioncontrasting
confidence: 77%
“…A similarity matrix was estimated using Dice’s coefficient, and a dendrogram was created based on the unweighted-pair group method with arithmetic averages. Enterococci isolates with a similarity coefficient ≥85% were considered as the same genotype ( Said & Abdelmegeed, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Enterococci isolates with a similarity coefficient ≥85% were considered as the same genotype (Said & Abdelmegeed 2019).…”
Section: Genotyping By Enterobacterial Repetitive Intergenic Consensumentioning
confidence: 99%